Give praise to God a vision of reforming worship : celebrating the legacy of James Montgomery Boice - Ryken, Philip Graham, 1966-; Thomas, Derek W.H., 1953-; Duncan, J. Ligon, III, 1960- (Phillipsburg, NJ Presbyterian and Reformed, 2003)
Includes bibliographical references.
Keywords: Public worship -- Reformed Church; Reformed Church -- doctrines